Development of ultra-high affinity bivalent ligands targeting the polo-like kinase 1. Issue 9 (27th July 2022) - Tsuji, Kohei; Hymel, David; Ma, Buyong; Tamamura, Hirokazu; Nussinov, Ruth; Burke, Terrence R.
Abstract : The polo-like kinase 1 (Plk1) is an important mediator of cell cycle regulation and a recognized anti-cancer molecular target. Abstract : The polo-like kinase 1 (Plk1) is an important mediator of cell cycle regulation and a recognized anti-cancer molecular target. In addition to its catalytic kinase domain (KD), Plk1 contains a polo-box domain (PBD), which engages in protein–protein interactions (PPIs) essential to proper Plk1 function. We have developed a number of extremely high-affinity PBD-binding peptide inhibitors. However, we have reached an apparent limit to increasing the affinities of these monovalent ligands. Accordingly, we undertook an extensive investigation of bivalent ligands, designed to engage both KD and PBD regions of Plk1. This has resulted in bivalent constructs exhibiting more than 100-fold Plk1 affinity enhancement relative to the best monovalent PBD-binding ligands. Startlingly, and in contradiction to widely accepted notions of KD–PBD interactions, we have found that full affinities can be retained even with minimal linkers between KD and PBD-binding components. In addition to significantly advancing the development of PBD-binding ligands, our findings may cause a rethinking of the structure – function of Plk1.